Identification of CMY-190, a novel chromosomally encoded AmpC β-lactamase, and plasmid-encoded KPC-2 in a clinical isolate of Citrobacter youngae - Liu, Zeshi; Shen, Siquan; Zhang, Xue; Lei, Jing; Tang, Chengkang; Wu, Shi; Lei, Ke; Yin, Jian; Zhang, Yanping; Guo, Yan; Geng, Yan; Hu, Fupin (Frontiers in Microbiology, 2025)
This study investigates the antibiotic resistance phenotype and genotype of Citrobacter youngae strain YS01, isolated from a peritoneal effusion sample, focusing on both chromosomal and plasmid-mediated resistance mechanisms to inform clinical antibiotic therapy. Our results reveal the presence of the chromosomally encoded β-lactamase CMY-190 and the plasmid-encoded carbapenemase KPC-2, which confer resistance to cephalosporins and carbapenems, respectively. CMY-190 exhibits substrate and inhibition profiles similar to AmpC β-lactamases and shares 88.05% amino acid identity with the plasmid-encoded enzyme CFE-2 from Citrobacter freundii pJA99. DNA sequence analysis identified the ampR gene upstream of both blaCMY-190 and blaKPC-2. In addition, genes identified surrounding the ampR–ampC regions in C. youngae, including ORF1, the fumarate operon (frdABCD), blc, and lolB, a DNA fragment not present in other Citrobacter species. The ampR–ampC genes were cloned into the PHSG398 vector and expressed in Escherichia coli DH5α, with the transformed strain showing partial resistance to cephalosporins. The blaKPC-2 was carried by Tn1721, previously identified mainly in Asian strains of Klebsiella pneumoniae. The expression of KPC-2 was confirmed by the conjugation of the donor bacterium C. youngae with E. coli J53 and by the transformation of the plasmid containing blaKPC-2 into E. coli DH5α, with all the transformed strains demonstrating resistance to carbapenems and elevated carbapenem MICs. To the best of our knowledge, this is the first report of a novel chromosomally encoded AmpC β-lactamase gene, blaCMY-190, and the emergence of blaKPC-2 in C. youngae.